Tanzania Economic Update, May 2016 : The Road Less Traveled – Unleashing Public Private Partnerships in Tanzania - World Bank Group (World Bank, Washington, DC, 2016)
The Tanzanian economy has grown at an average annual rate of around 6-7 percent for more than a decade. The rate of inflation has declined since January 2016, although it trended upwards in thepreceding few months due to increases in domestic food prices and the lagged impacts of the sharp depreciation of the Tanzanian Shilling during the first half of 2015. However, the Shilling stabilized in the second half of 2015, with the real exchange rate now close to the equilibrium level. The current account deficit has also improved, standing at around 8.7 percent of GDP in 2014/15. The level of aid inflows declined during 2014/15, although this was offset by increases in FDI and external non-concessional borrowing, maintaining the overall balance of payments in a stable position. Tanzania's infrastructure and social services deficits are already massive and projected to increase into the future. Traditional financing instruments are clearly insufficient to bridge the profound gap between existing public resources and financing requirements. By leveraging synergy between the public and private sectors, PPPs can mobilize additional sources of finance to fund the development of vitally needed infrastructure; to deliver on budget and on time to a greater extent than in the case of publicly financed projects; and to deliver higher quality services than in the case of publicly managed projects. Tanzania’s own policy documents identify PPP as a key instrument to attract new investment and to deliver infrastructure more efficiently.